Development of Functional Beverage Based on Taste Preference - Bhuiyan, MHR; Shams-Ud-Din, M; Islam, MN (Journal of Environmental Science and Natural Resources, 2012)
The experiment was conducted to develop functional beverage based on taste preference and studied its storage life. 32 full factorial design was used to identify significant factor and base formulation. The one factor at a time optimization method was used to optimize formulation. The study showed that sweetness, sourness and their interaction have significant effect on overall acceptability in the development of functional beverage. Optimal combination per liter of functional beverage for men was found to be 73 mg saccharin and 30 ml of lime juice. For women, however, the optimal combination of each liter of functional beverage was 60 mg saccharin and 47.5 ml lime juice. Honey, garlic paste, black cumin seed powder, Sodium-benzoate, ascorbic acid, annatto color, citral, methyl phenyl acetate and water was common ingredients. Organoleptic taste test indicated that men and women preferred sweet and sour beverage respectively. TSS and pH showed linear whereas acidity and vitamin C concentration showed inverse relation with storage period. The RFT (4±1°C) storage ensured better retention of chemical and sensory properties than RMT (30±2°C) storage. Significant storage (RFT) life of functional beverage for men and women was 5 to 6 and 4 to 5 months, respectively. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11558 J. Environ. Sci. & Natural Resources, 5(1): 83 - 87, 2012